PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI TENTANG STATISTIKA DENGAN METODE SYNDICATE GROUP - djumiatun djumiatun; Erlin Suliztiana (Tunas Nusantara, 2023)
The purpose of this research is to analyze the enhancement of the VI A students of Public Elementary School 4 Kutoharjo learning outcomes of Mathematic about Statistic on the Second Semester of 2021/2022 Academic Year with Syndicate Group Method. This is a Classroom Action Research (CAR). The place of this research is on the VI A Class of Public Elementary School 4 Kutoharjo. The time of this research is the middle period on the Second Semester of 2021/2022 Academic Year. The subjects are consisting of 10 boys and 24 girls. The data of this research is learning outcomes of the subjects. Techniques of collecting data are nontest and test. Tools of collecting data are written test and observation sheet. The result is learning outcomes enhanced from unsatisfactory category to satisfying.Keywords: Learning Outcomes, Mathematic, Statistic, Syndicate Group Method